KAJIAN NORMATIF TERHADAP KEBIJAKAN PEMUTUSAN HUBUNGAN KERJA (PHK) DALAM SITUASI KRISIS EKONOMI - Lamonsya, Muhamad Nabil; Fatriani, Fenny (LPPM Universitas Bina Bangsa, 2025)
During economic crises, where companies are forced to lower their operating costs, layoffs are a frequent problem. Using a normative approach, this study aims to analyze policies related to termination of employment (PHK) in Indonesia. This study examines the conformity of termination policies with applicable regulations, such as the Manpower Law and other relevant regulations, as well as the principle of fairness for employers and workers. Layoffs are often the last resort in economic crisis situations, but they often cause conflicts of interest between companies and workers. The study found that the termination of employment policy (PHK) must be implemented for clear reasons and in accordance with legal procedures. In addition, they must consider the balance between business continuity and the protection of workers' rights.